PENGARUH PENGGUNAAN MEDIA KOMUNIKASI (PRESENTASI) TERHADAP DAYA SERAP NELAYAN DI KELURAHAN BONTAG KUALA, KOTA BONTANG - Rizky Nurliana Astuti; Said Abdussyahid; Fitriyana (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
Research was aimed to find out if the counseling activities conducted positively affect the absorption of fishermen and to know the level of absorption of fishermen to the counseling activities (presentation) that have been carried out. This research was conducted in Bontang Kuala Village, Bontang City using sample method based on census (30 fishermen became respondents). The results of the analysis showed that the use of communication media (presentation) to the absorption of fishermen had a positive effect with scores of 7.86 and 9.6, respectively. The score belongs to the moderate category where the counseling activities conducted have been running well and have a positive impact for fishermen in Bontang Kuala Village although not yet fully maximized. Keyword: Use of media, communication, absorption